مساهمة في دراسة توزع ثنائي المصراع Mytilidae): Brachidonta variabilis(Bivalvia وصفاته الكمية في المنطقة الشاطئية Littoral لمدينة بانياس - صقر, فائز; المصري, محمد; صالح, محمد (Latakia University Journal -Biological Sciences Series, 2019)
يتناول هذا البحث ولأول مرة توزع ثنائي المصراع Brachidonta variabilis (Krauss, 1962) وصفاته الكمية في المنطقة الشاطئية Littoral لمدينة بانياس في سبعة مواقع, وهذا النوع يؤدي دورا" هاما" في النظام البيئي البحري لأن تجمعاته تشكل ملجأ" بيئيا" طبيعيا" لمختلف الأحياء البحرية, فهو يحتاج إلى التعمق في دراسته من الناحية البيئة والتوزع, وقد بينت هذه الدراسة بأن نمط توزعه هو توزع تجمعي لأن علاقة التشتت علـى المتوسط الحسابي()وقيم دليل موريسيتا كانت دائما" أكبر من الواحد وهذا مايؤكد التوزع التجمعي لهذا النوع, كما أن قيم >1, إذ بلغت أعلى القيم(13.726) في الموقع D وأدنى القيم(2.402) في الموقعF وهذا دليل على تطابق التوزع التجريبي مع التوزع التجمعي, وبينت النتائج أن أعلـى قيمـة للكتلة الإحيائية والغزارة للنوع المدروس كانت في الموقع(D)وبلغت(9146 غ/م2) وعـدد الأفراد(7484فردا"/م2) بسبب الدور الايجابي للمياه الساخنة الناتجة عن المحطة الحرارية وأخفض قيمة فـي الموقع (G) بلغت(3234غ/م2) وعـدد الأفراد(2566فردا"/م2) بسبب الدور السلبي للملوثات النفطية في هذا الموقع. This study deals (for the first time) with the distribution of bivalve (Brachidonta variabilis) and its qualitative properties on seven sites in the littoral zone of Banias city. This species of bivalvia plays an important role in the marine ecosystem because its accumulates form a natural environmental shelter for various marine lives; it is necessary to do an in-depth environmental and distributional study. This study showed that the distribution of this bivalve is accumulative because the relation between the factor of dispersion and average (Iδ2/x) and the index Morisista values was > 1, which confirms the accumulative distribution of this species. In addition, the values of Iδ2/x were > 1, the largest values were 13.726 on D site, and the minimum values were 2.402 on F site, which indicate the coincidence between the accumulative and experimental distribution. The results showed that the maximum values for biomass and abundance concerning studied species were on D site (9146 g/m2), and the number of individuals was 7484 Ind / m2. These results can be attributed to the hot water coming from the hydrothermal station. Moreover, the minimum values on G site were 3234 g/m2 and the number of lives were 2566 Ind /m2, according to the negative role of oil polluted compounds on this site of study.